2017
DOI: 10.1007/s00540-017-2306-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of acute changes in perfusion index and blood pressure on the accuracy of non-invasive continuous hemoglobin concentration measurements during induction of anesthesia

Abstract: The findings suggest that blunting the increase in PI by maintaining arterial pressure during induction of anesthesia improves the agreement between SpHb and tHb values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
3
3
0
Order By: Relevance
“…Furthermore, Michel and Phillips 18 showed that an abruptly lowered capillary pressure caused an reabsorption of fluid from the tissues to the capillary, which supports our finding of a hypotension‐induced transient fluid absorption. Finally, we have in a previous study reported a similar decrease in Hct and an increase in PV in parallel to a decrease in MAP, 15 which is in line with studies by Sano and Saito 19,20 …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, Michel and Phillips 18 showed that an abruptly lowered capillary pressure caused an reabsorption of fluid from the tissues to the capillary, which supports our finding of a hypotension‐induced transient fluid absorption. Finally, we have in a previous study reported a similar decrease in Hct and an increase in PV in parallel to a decrease in MAP, 15 which is in line with studies by Sano and Saito 19,20 …”
Section: Discussionsupporting
confidence: 91%
“…No adverse effects were encountered during the study protocol on heart rate, ST-segment, cerebral oxygenation or arterial lactate. 19,20 Our data on TER, the disappearance rate of radiolabelled albumin from plasma, are in line with previous studies showing a diffusion of albumin over endothelial structures with a rate of 5.0%…”
Section: Ta B L E 1 Patient Demographics and Characteristicssupporting
confidence: 91%
See 1 more Smart Citation
“…Pulse CO-Oximetry is a promising technique that provides noninvasive, continuous detection of anemia but cannot be used as a substitute for invasive Hb measurements. Multiple factors, such as serious anemia and large amounts of vascular drugs leading to poor peripheral perfusion [11, 12], can reduce the accuracy of SpHb monitoring. We also found the decreased accuracy during blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…Although radial blood flow decreased immediately and recovered 5 min after cannulation, blood flow reduction at the fingertip may have occurred because the diameters of the radial artery or its dorsal branch significantly decreased after cannulation [ 26 , 27 ]. Fourth, SpHb with PI of <1.0 should be excluded from the final analysis because the decrease in PI after phenylephrine administration reduced the changes in the bias values after anesthesia induction [ 9 ].…”
Section: Discussionmentioning
confidence: 99%